Challenging authority : how ordinary people change america - Piven, Frances Fox (Polemics., 2008)
Challenging Authority argues that ordinary people exercise real power in American politics mainly at those extraordinary moments when they rise up in anger and hope, defy the rules that ordinarily govern their daily lives, and by doing so, disrupt the wor.